Modifications of the mini-flotac technique used on cattle and sheep feces to facilitate its use in field routines - de Paiva, Vinícius Vieira; Aguiar, Lívia Mendonça de; Vieira, Gismar Silva; Rosalinski-Moraes, Fernanda (Revista Acadêmica Ciência Animal, 2021)
The purpose of this study is to compare the Gordon and Whitlock (GW) and mini-FLOTAC (MF) egg counting techniques in order to propose modifications of the latter, which is a current and more sensitive egg counting technique. The idea was to read only one compartment of the MF chamber, and also to propose a model to enable the use of the fill-FLOTAC (FF) device for sheep feces. To this end, strongylid eggs per gram of feces (EPG) were counted using a pool of cattle and sheep feces. The results indicated that there was no significant difference between the proposed methods, except for the use of the FF device for sheep fecal pellets without first weighing the sample or the use of a correction factor of 2.6. Reading only one compartment of the MF device, using the fill-FLOTAC device to perform the test renders the mini-FLOTAC technique more efficient in counting eggs per gram of feces than the Gordon and Whitlock method.